Employee Spirit: The Influence of Leadership Style and Work Environment: Study on Education and Culture Service Serang District - Rohaelis Nuraisiah; Anggi Haerani (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2022)
The method used in this study is quantitative. This method uses to predict the influence between the independent variable and the dependent variable; in this study, the variable X1 (Leadership Style), X2 (Work Environment) is the independent variable and the variable Y (Work Spirit) is the dependent variable. The sample in this study was 70 people; the instrument used was primary data, and multiple linear regression analysis uses to analyze the data. Based on the results of the study, there is a significant influence between leadership style and work environment on employee morale at the Education and Culture Office of Serang Regency. With the test results obtained multiple linear regression equation Y= 28.019 + 0.215 X1 + 0.246 X2. and hypothesis testing, the value of tcount Leadership Style = 2.312, using the significant limit = 0.05, obtained ttable = 1.66757. Moreover, tcount Work Environment = 4.034 obtained ttable = 1.66757. The test criteria from these results are tcount > ttable, meaning H0 reject, and H1 is accepted. Thus, the t-test hypothesis of the leadership style variable and work environment significantly influence work motivation. The leadership style variable has a coefficient of determination of 0.215, which means there is an influence of leadership style. It works environment on employee morale by 21.5%, and the remaining 78.5% influenced by variables others not included in this study.